Chemical Identification of Catalytically Active Sites on Oxygen‐doped Carbon Nanosheet to Decipher the High Activity for Electro‐synthesis Hydrogen Peroxide. (17th June 2021) - Chen, Shanyong; Luo, Tao; Chen, Kejun; Lin, Yiyang; Fu, Junwei; Liu, Kang; Cai, Chao; Wang, Qiyou; Li, Huangjingwei; Li, Xiaoqing; Hu, Junhua; Li, Hongmei; et al.
Abstract: Electrochemical production of hydrogen peroxide (H2 O2 ) through two‐electron (2 e − ) oxygen reduction reaction (ORR) is an on‐site and clean route. Oxygen‐doped carbon materials with high ORR activity and H2 O2 selectivity have been considered as the promising catalysts, however, there is still a lack of direct experimental evidence to identify true active sites at the complex carbon surface. Herein, we propose a chemical titration strategy to decipher the oxygen‐doped carbon nanosheet (OCNS900 ) catalyst for 2 e − ORR. The OCNS900 exhibits outstanding 2 e − ORR performances with onset potential of 0.825 V (vs. RHE), mass activity of 14.5 A g −1 at 0.75 V (vs. RHE) and H2 O2 production rate of 770 mmol g −1 h −1 in flow cell, surpassing most reported carbon catalysts. Through selective chemical titration of C=O, C−OH, and COOH groups, we found that C=O species contributed to the most electrocatalytic activity and were the most active sites for 2 e − ORR, which were corroborated by theoretical calculations. Abstract : The oxygen‐doped carbon nanosheet (OCNS900 ) has been demonstrated as highly effective catalyst for electrosynthesizing hydrogen peroxide with mass activity of 14.5 A g −1 at 0.75 V (vs. RHE) and H2 O2 production rate of 770 mmol g −1 h −1 in a flow cell. Chemical titration and DFT calculations were used to decipher the high activity for hydrogen peroxide production; the C=O groups are identified as the most active sites.